New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine - Trach, Viacheslav A. (Zootaxa, 2016)
A new species of the family Halolaelapidae (Acari: Mesostigmata), Halolaelaps euxinus sp. nov. is described from Black Sea coast. Adult mites were found in seaweed, while deutonymphs were collected from the amphipod Talorchestia deshayesii and from seaweed. The adult female of Halolaelaps saproincisus Hirschmann & Götz, 1968 is recorded in new localities of Ukraine for the first time, in soil and bird faeces in chicken coops, and new morphological information is provided. The adult male (collected from chicken coops) and the deutonymph (collected from chicken coops and on dung-beetles) of H. saproincisus are described for the first time.